Towards Optimized Acquisition Scheme for Multi-projection Correlation Imaging of Breast Cancer - Chawla, Amarpreet S. (2009)
RATIONALE AND OBJECTIVES: Correlation Imaging (CI) is a form of multi-projection imaging technique in which multiple images of a patient are acquired from slightly different angles. Information from these images is combined to make the final diagnosis. A critical factor affecting the performance of CI is its data acquisition scheme since a non-optimized acquisition may quickly distort the pathological indicators. In this article, we are presenting a Computer Aided Detection (CADe)-based methodology to optimize the acquisition scheme of CI towards superior diagnostic accuracy. MATERIALS AND METHODS: Images from 106 subjects were employed. For each subject, 25 angular projections of a single breast were acquired. Projection images were supplemented with a simulated 3 mm 3D lesion. Each projection was then processed by a traditional CADe algorithm at high sensitivity, followed by reduction of false positives by combining geometrical correlation information available from the multiple images. Performance of the CI system was determined in terms of free-response receiver operating characteristic (FROC) curves and the area under the ROC curves. For optimization, the components of acquisition such as the number of projections, and their angular span were systematically changed to investigate which one of the many possible combinations maximized the obtainable CADe sensitivity and specificity. RESULTS: Performance of the CI system improved by increasing the angular span. Increasing the number of angular projections beyond a certain number does not improve performance. Maximum performance was obtained between 7–10 projections spanning our maximum angular arc of 45°. CONCLUSION: Findings suggested the existence of an optimum acquisition for CI of the breast. CADe-based results confirmed earlier predictions based on observer models. Optimized CI system may potentially be an important diagnostic tool for improved breast cancer detection.